JUEGOS MOTRICES PARA MEJORAR LA MOTRICIDAD EN NIÑOS DE 9 A 10 AÑOS DE LA UNIDAD EDUCATIVA “ADOLFO MARIA ASTUDILLO ”, - MONTIEL CARRIEL JOSE LUIS (2024)
The research was carried out with the purpose of developing an instruction manual that serves as support to develop the problem within the institutional context regarding motor games to improve motor skills in children from 9 to 10 years old in the “Adolfo María Astudillo” educational unit. ”, which was justified in each of the theoretical sections described by several authors who indicate that motor games can meet motor skills and abilities in addition to cognitive, affective and social skills. The research methodology was field, descriptive, with a mixed approach, the population and sample were defined to apply the observation sheet and the motor tests, the results were poor evidenced in the discussion, so the proposal was developed of the motor games guide where each of the games were described with their respective structure to comply with the improvement of different motor skills and abilities. The application of the tests was to know the degree of development of motor skills. The tabulation of the information will be carried out using spreadsheets in Excel and SPSS Statistics for detailed processing. The analysis and interpretation of data will focus on the results obtained from the surveys and measurements, providing a comprehensive vision of the participation and perceptions of children in motor games in the “Adolfo María Astudillo” Educational Unit.